The Relationship Between Coping Strategy And Social Support With Caregiver Burden In Parents/ Caregivers Of Down Syndrome In Surabaya - LUKUT, Monika; YUNIAR, Sasanti Yuniar; FITHRIYAH, Izzatul Fithriyah (International Journal of Environmental, Sustainability, and Social Science, 2021)
The goal of this study was to analyze the relationship between coping strategies and social support with caregiver burden in parents/caregivers Down syndrome in Surabaya. Method: The method used is the design of observational analytical research, cross sectional, against parents or caregivers of Down syndrome in Surabaya. Ways of Coping Questionnaire (WCQ) instrument to measure coping strategies, The Multidimensional Scale of Perceived Social Support (MSPSS) for measuring social support, and Caregiver Burden Assessment (CBA) to measure caregiver burden. Statistical analysis uses correlation tests. Results: The study sample was 37 parents / caregivers of children with Down syndrome in Surabaya. The results obtained by parents / caregivers Down syndrome dominantly using coping focused on emotions (89.4%). High levels of social support were felt by parents/caregivers (51.4%) and the total burden of parents/caregivers was low and very low (64.8%). The results of the analysis between coping strategy with caregiver burden, and social support analysis with caregiver burden, did not get a meaningful relationship (p>0.05). Research found a meaningful relationship between parents/caregivers who have severe problems and the level of independence ana k Down syndrome with caregiver burden (p<0.05). Discussion: From the above results it can be concluded that there is no meaningful relationship between coping strategy and social support with caregiver burden in parents / caregivers of Down syndrome. Caregiver burden is more related to the condition of parents who have severe problems in the last 6 months and the level of independence of children Down syndrome.